Professional learning in organizing students’ activities of teaching latin american literature in HCMC University of Education – linguitics and literature department - Nguyen , Thanh Trung (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
Modern life and society demand that education must improve regularly and continuously. In the context of teacher-centered and student-centered models of education gradually reveal many shortcomings, the orientation of professional learning is born to take students’ result as center; the role of teachers, learners and curriculum, thereby, are considered carefully again. This article presents the concept of professional learning in a broad sense which includes three of those components through the task of organizing activities in the Latin American Literature class. On that base, a number of ideas for training and improving teacher are presented and discussed.